The state of state reform in Latin America - Lora, Eduardo (Latin American development forum., 2007)
Latin America suffered a profound state crisis in the 1980s, which prompted not only the wave of macroeconomic and deregulation reforms known as the Washington Consensus, but also a wide variety of institutional or "second generation" reforms. The State of State Reform in Latin America reviews and assesses the outcomes of these less studied institutional reforms. This book examines four major areas of institutional reform: a) political institutions and the state organization; b) fiscal institutions, such as budget, tax and decentralization institutions; c) public institutions in char.